Loneliness and adaptation among second-generation portuguese migrants to France: roles of perceived responsability and control - Félix Neto (2000)
This study explores the association of perceived responsibility fur loneliness and perceived control over loneliness on social adaptation and psychological adaptation among 109 second-generation Portuguese migrants to France. Analysis showed that rated perceived control was more highly associated with scores on social adaptation and psychological adaptation than perceived responsibility.